PLATFORM LAYANAN PENGANTARAN MAKANAN DAN JASA TRANSPORTASI BERBASIS WEBSITE - Nailah Salsabila; Jose Elio Parhusip; Y. Casmadi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
An integrated service platform that provides food delivery and transportation services with a website concept is a promising solution to meet the needs of a practical and efficient modern lifestyle. The research aims to design and develop a responsive and user-friendly website-based platform, so that users can easily access both services through a single centralized gateway. The platform also provides cash payments. By implementing a modern and responsive website concept, it is expected to provide optimum user experience, increase efficiency, and be an integrated solution for food delivery and transportation needs in one system